Large-area nanostructured surfaces with tunable zeta potentials. (June 2020) - Al Hossain, Aktaruzzaman; Yang, Mengying; Checco, Antonio; Doerk, Gregory; Colosqui, Carlos E.
Graphical abstract: Highlights: Nanostructures surfaces with large area (1 cm × 2 cm) are fabricated via block copolymer self-assembly. Zeta potentials of nanostructured superhydrophobic OTS surfaces are measured for different pH and electrolyte concentration. Flat and nanostructured surfaces show similar zeta potentials for very low Dukhin numbers. At large Dukhin numbers superhydrophilic surfaces show weaker zeta potentials. Superhydrophobic surfaces with large hydrodynamic slip report negative zeta potentials up to − 80 mV. Abstract: Through a refined fabrication protocol based on block-copolymer self-assembly we synthesize nanostructured surfaces with conical nanopillars of different height (60, 120, and 200 nm) in hexagonal arrays with uniform spacing ( ∼ 50 nm) over large areas ( > cm 2 ). While the nanostructured surfaces fabricated on silicon substrates display superhydrophilic behavior, superhydrophobic properties are attained by coating with octadecyltrichlorosilane (OTS). Negative zeta potentials for all the studied surfaces are reported by electrokinetic flow measurements with aqueous KCl solutions at different concentrations (1 and 10 mM) and pH values between 4 and 8. While the surface nanostructure reduces the zeta potential magnitude, the hydrophobic OTS coating enhances it. Experimental results can be accounted for by a site-dissociation model for the surface charge density. The reported wetting properties and zeta potential tunability makes the studied surfaces particularly relevant for applications such as energy conversion and storage, membrane-based water treatment and molecular separation.